Twins Ionospheric Links in Sudan and South Sudan Based on University of Khartoum Ionospheric Shells (UKIS) (University of Khartoum Engineering Journal, 2022)
The concept of UKIS is revised, illustrated graphically and represented by mathematical equations. Fivecities have been chosen for this study: Khartoum, Wadihalfa, Nimule, Kassala and AlJunaynah. The concept of twinionospheric links is introduced and different parameters for Twin links were studied. The relation between Twin linksand UKIS is illustrated. Contour maps that show the strength and death time of UKIS for the country are attached tothe paper. The study is based on empirical ionospheric modeling and the statistics are computed using theInternational Reference Ionosphere model (IRI).